2018
DOI: 10.1002/epi4.12104
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy after perinatal stroke with different vascular subtypes

Abstract: SummaryObjectiveWith an incidence up to 63 per 100,000 live births, perinatal stroke is an important cause of childhood epilepsy. The aim of the study was to find the prevalence of and predictive factors for epilepsy, and to describe the course of epilepsy in children with perinatal stroke with different vascular subtypes.MethodsPatients were retrieved from the Estonian Paediatric Stroke Database with follow‐up time at least 24 months. Patients were divided into 5 perinatal stroke syndromes: neonatal arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 31 publications
(56 reference statements)
1
36
0
2
Order By: Relevance
“…Early cerebral injury affects numerous cortical circuits such as the corticothalamic connections 109 and this may contribute to the pathogenesis of seizures for the approximately 25% of fetuses with PVHI who went on to develop seizures or epileptic encephalopathies. In children presenting with PVI outside the perinatal period, seizures were the presenting complaint in 6% to 17%, consistent with our findings 97,119 . The epilepsy rate of 25% is also comparable to common varieties of perinatal stroke in term‐born children 119 where it has been associated with adverse neurodevelopmental outcomes, 120,121 suggesting this may be a modifiable determinant of outcome from fetal GMH‐IVH.…”
Section: Discussionsupporting
confidence: 86%
“…Early cerebral injury affects numerous cortical circuits such as the corticothalamic connections 109 and this may contribute to the pathogenesis of seizures for the approximately 25% of fetuses with PVHI who went on to develop seizures or epileptic encephalopathies. In children presenting with PVI outside the perinatal period, seizures were the presenting complaint in 6% to 17%, consistent with our findings 97,119 . The epilepsy rate of 25% is also comparable to common varieties of perinatal stroke in term‐born children 119 where it has been associated with adverse neurodevelopmental outcomes, 120,121 suggesting this may be a modifiable determinant of outcome from fetal GMH‐IVH.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, a recent study found a lower incidence of epilepsy in periventricular venous infarction than perinatal arterial stroke; however, the 2 cases of epilepsy associated with periventricular venous infarction in the report led to refractory epileptic encephalopathies. 12 The relative sparing of cortical gray matter in periventricular venous infarction is thought to underlie the lower rates of epilepsy and cognitive sequelae. 13 However, the extensive number of epileptic spasms etiologies suggests a pathologic network that can be influenced at multiple brain regions, including cortex, subcortical structures, and brain stem, and often involve multiregional abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of seizures after perinatal stroke on cognition is still unclear, though it is more significant that epilepsy correlates with cognitive impairment. 12 Epileptic spasms, particularly in symptomatic cases including perinatal strokes, often leads to poor developmental outcomes. 27 Further studies are necessary to not only elucidate the effect of epileptic spasms on cognitive outcome in this population but to also assess whether rapid and successful treatment alters this course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations